Grading Goal Four Tensions, Threats, and Opportunities in the Sustainable Development Goal on Quality Education - Wulff, Antonia (Brill, 2020)
Grading Goal Four explores the tensions, threats and opportunities within Sustainable Development Goal 4 on quality education, aiming to support its rights-based implementation and to build capacity for strengthened monitoring and analysis of the goal.; Readership: All interested in the threats and opportunities within SDG 4 on quality education, including researchers, students and education activists in academia, civil society, government policy-making and international educational diplomacy.